Prediction of Ultimate Moment Capacity of Steel-Concrete Composite Beams Using Artificial Neural Networks - Mtashet, Rana A.; Jasim, Nabeel A.; Alwan, Majid A. (Basrah Journal for Engineering Sciences, 2013)
The paper deals with neural networks identification of ultimate moment capacity of steel-concrete composite beams on base of experimental results. Basic information on artificial neural networks and its parameters suitable for analysis of experimental results are given. Two types of neural network algorithms are used. Results of identification are reported. The results show that artificial neural networks are highly suitable for assessing the ultimate moment capacity of composite section. The proposed neural network was also used to explore the effect of the various parameters on the behaviour of composite beams.